2020
DOI: 10.3390/jcm9092782
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Association of Desacyl-Ghrelin with Physical Activity and Chronic Food Restriction: A Translational Study on Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is a severe metabopsychiatric disorder characterised by caloric intake restriction and often excessive physical exercise. Our aim is to assess in female AN patients and in a rodent model, the co-evolution of physical activity and potential dysregulation of acyl—(AG) and desacyl—(DAG) ghrelin plasma concentrations during denutrition and weight recovery. AN inpatients were evaluated at inclusion (T0, n = 29), half—(T1) and total (T2) weight recovery, and one month after discharge (T3, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…The two different approaches (change from baseline to follow-up and follow-up to HCs) were repeated for a longitudinal analysis of acyl ghrelin values. Longitudinal analysis of acyl ghrelin in five studies [ 67 , 69 , 74 , 78 , 79 ] provided data at seven follow-up time points, including a total of 77 AN patients (providing 135 data points). Four studies included patients in an inpatient setting, including a nutritional rehabilitation program (n = 2) and nutritional program combined with cognitive behavioural therapy (n = 2) and one study did not provide treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two different approaches (change from baseline to follow-up and follow-up to HCs) were repeated for a longitudinal analysis of acyl ghrelin values. Longitudinal analysis of acyl ghrelin in five studies [ 67 , 69 , 74 , 78 , 79 ] provided data at seven follow-up time points, including a total of 77 AN patients (providing 135 data points). Four studies included patients in an inpatient setting, including a nutritional rehabilitation program (n = 2) and nutritional program combined with cognitive behavioural therapy (n = 2) and one study did not provide treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, results of the current meta-analysis also showed significant increases in acyl ghrelin during the acute state, possibly opposing this theory. Moreover, one study showed desacyl ghrelin to be particularly associated with BMI and physical activity [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AN, plasma variations of AG and DAG during the weight restoration period might be considered as reliable biomarkers of a successful recovery [ 31 ]. Indeed, we recently showed that DAG plasma concentration after weight restoration is associated with instable recovery and an increase in physical activity after discharge [ 32 ]. However, an accurate measurement of physical activity in AN remains difficult and data are still lacking, limiting translational benefits from preclinical models such as the activity-based rodent model of AN [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address this important health issue, the current Special Issue collected 21 articles examining the most recent and relevant scientific findings regarding advances in ED. The published articles comprised three reviews and 18 research articles focusing on different aspects, such as genetic [ 7 ] and epigenetic factors [ 8 ], biomarkers [ 9 ], comorbidity [ 10 , 11 , 12 , 13 , 14 ], clinical phenotypes [ 15 , 16 ], neurocognition [ 12 , 17 , 18 , 19 , 20 , 21 ], treatment predictors [ 22 ], and treatment models and therapeutic targets [ 19 , 23 , 24 , 25 , 26 , 27 ]. Altogether, these studies may provide increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.…”
mentioning
confidence: 99%
“…The identification of biomarkers was also a relevant topic addressed in this issue. Duriez et al [ 9 ], in a translational study, aimed to determine whether some biomarkers, such as acyl-ghrelin (AG) and desacyl-ghrelin (DAG) plasma concentrations, reflect the level of physical activity during food restriction and after renutrition. Authors found that, in experimental models of mice, AG and DAG both increased during food restriction.…”
mentioning
confidence: 99%